Case report: Methemoglobinemia caused by nitrobenzene poisoning - Zhao, Liwen; Jian, Tianzi; Shi, Longke; Li, Yaqian; Wen, Zixin; Guo, Lanlan; Li, Qilu; Jian, Xiangdong (Frontiers in Medicine, 2023)
Nitrobenzene poisoning is uncommon, with most cases occurring in the dye, paint, and other chemical industries. Nitrobenzene enters the body mainly through the skin, respiratory tract, and oral cavity. Nitrobenzene poisoning symptoms include hypermethemoglobinemia, hemolytic anemia, liver and kidney dysfunction, cardiogenic pulmonary edema, and toxic encephalopathy, which endanger people’s lives. Therefore, we present a case of nitrobenzene poisoning caused by skin absorption, focusing on its clinical characteristics and treatment outcomes. A 58 years-old man presented to our department with confusion and cyanosis. He has a history of hypertension and cerebral infarction. The patient was diagnosed with moderate occupational acute benzene poisoning with nitro compounds. Symptomatic support, methylene blue, and other antioxidant treatments were commenced after diagnosis. After treatment, the patient’s condition gradually improved, and he was discharged.